Early Growth Performance of Seedlings and Saplings in Sarawak Botanical Garden - Bridgette, Philip (Universiti Malaysia Sarawak (UNIMAS), 2017)
Sarawak Botanical Garden is a 206 acres area and are planted with the endemic trees species of Borneo. However, the survival rate and health status of the seedlings and saplings are not known. Hence, this study was initiated to determine the species composition, diameter at breast height, planting distance, health status through visual assessment, chlorophyll content and the stomata density of the seedlings. Five plots of 25 m x 25 m were established, species were identified and the number of seedlings were counted. Thirty-six (36) species from fourteen (14) families were planted in the Fruit Orchard of the Sarawak Botanical Garden. Some of the dominant species were Baccaurea angulata, Pometia pinnata and Lansillm domesticllm. The most dominant families recorded were Anacardiaceae, Euphorbiaceae, and Moracea. Within the period of three (3) to four (4) months, some seedlings observed were dead and the lowest mortality rate recorded were from the Artocarpus integer, Baccaurea motleyana, Garcinia mangostana and Mangifera griffithii. Pometia pinnata recorded the highest mortality rate. Most of the seedlings SP AD index recorded below 35 with only one or two seedlings from each species recorded above 55, while the rest were moderate. L. pussilus and S. grande unshaded leaves had lower number of stomata compared to the shaded leaves. Pometia pinnata and Artocarpus integer recorded five (5) seedlings or saplings categorized as healthy based on visual assessment. Most of the seedlings died probably due to insufficient planting space and improper drainage in the garden. Data collected will help future management and proper planting strategies in the Sarawak Botanical Garden.